2020
DOI: 10.3390/ph13100297
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Cholinergic Circuits as an Area for Targeted Drug Treatment of Alzheimer’s Disease: In Vivo Assessment of Short-Term Plasticity in Rat Brain

Abstract: The search for new therapeutics for the treatment of Alzheimer’s disease (AD) is still in progress. Aberrant pathways of synaptic transmission in basal forebrain cholinergic neural circuits are thought to be associated with the progression of AD. However, the effect of amyloid-beta (Aβ) on short-term plasticity (STP) of cholinergic circuits in the nucleus basalis magnocellularis (NBM) is largely unknown. STP assessment in rat brain cholinergic circuitry may indicate a new target for AD cholinergic therapeutics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…The statistiscal significance of the heterogeneity of interspike intervals (or spike frequency) of the pre- and post-stimulus impulse flow was analyzed by the Student's t - test and Mann–Whitney U test. Thus, we recorded single-cell spiking short-term dynamics of a large range, which are presynaptically induced by HFS and these results confirm the view, that in a large-size network, STP can greatly enrich the network's dynamical behaviors 62 .
Figure 9 ( A ) In vivo recorded spike flow of single neuron in mPFC.
…”
Section: Methodssupporting
confidence: 77%
See 1 more Smart Citation
“…The statistiscal significance of the heterogeneity of interspike intervals (or spike frequency) of the pre- and post-stimulus impulse flow was analyzed by the Student's t - test and Mann–Whitney U test. Thus, we recorded single-cell spiking short-term dynamics of a large range, which are presynaptically induced by HFS and these results confirm the view, that in a large-size network, STP can greatly enrich the network's dynamical behaviors 62 .
Figure 9 ( A ) In vivo recorded spike flow of single neuron in mPFC.
…”
Section: Methodssupporting
confidence: 77%
“…Intra-population variance ratio between time intervals during HFS and post-stimulation compared to baseline was calculated using Student’s t -test. The statistical significance between control and VPA-treated groups was estimated according to chi-square and Fisher’s exact tests 62 .…”
Section: Methodsmentioning
confidence: 99%
“…The increased levels of endogenous Aβ enhances the initial release probability at the CA3-CA1 synapses of the hippocampus, which, in turn, destructs the vesicles and affects the synaptic short-term plasticity and the firing probability of the CA1 output neuronal synapse [15,16]. In our previous study, we have already shown the disruption of short-term plasticity in nucleus basalis magnocellularis (NBM) hippocampus and NBM-basolateral amygdala cholinergic circuits [17]. In contrast to the deficits seen in cholinergic and glutamatergic systems, the non-significant change of TD-PTD response pattern after amyloid exposure can be due to the fact that GABAergic neurons and receptors appear more resistant to neurodegeneration during AD [18].…”
Section: Discussionmentioning
confidence: 94%